Superoxide dismutase and glutathione peroxidase content in children with type 1 diabetes mellitus - Yu. V. Bykov; V. A. Baturin (Сибирский научный медицинский журнал)
Type 1 diabetes mellitus (T1D) is one of the most frequently diagnosed chronic diseases of childhood. Oxidative stress (OS) is considered as one of the possible mechanisms of its development and complications. The aim of the study was to analyze the content of the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GP) in children and adolescents with adequately controlled T1D.Material and methods. A total of 58 children were examined, including 34 children with type 1 diabetes (study group) and 24 conditionally healthy children (control group). The content of glycated hemoglobin, blood plasma glucose per day, post-prandial glucose, total protein, creatinine and urea were determined by conventional methods, as well as the level of SOD and GP in the blood serum by ELISA.Results and discussion. A significant decrease in the content of both enzymes was found in type 1 DM patients compared to conditionally healthy children. In patients with the chronic form of the disease, SOD and GP level was significantly lower than in patients with incident T1D. An inverse correlation was revealed between the antioxidant enzymes level on the one hand and age, duration of the disease, and the number of episodes with a poor glucose history on the other hand. The decrease in SOD and GP concentration was associated with an increase in glycated hemoglobin and plasma glucose level over a 24-hour period in patients with chronic type SD 1. The decrease in SOD concentrations was associated with an increase in glycated hemoglobin in patients with T1D chronic type. The discovered abnormalities indicate that decreased antioxidant enzyme level represent a manifestation of OS in patients with adequately controlled type 1 DM.Conclusions. Content of antioxidant enzymes in children with T1D provides an important criterion for the assessment of OS manifestations in this disease.